S133 Breathlessness post-drainage predicts survival in patients with malignant pleural effusion. (December 2018) - Mishra, EK; Murugananandan, S; Clive, AO; Davies, HE; Stanton, AE; Wrightson, JM; Bhatnagar, R; Psallidas, I; Maskell, NA; Lee, YCG; Miller, RF; Rahman, NM
Abstract : Introduction: Malignant pleural effusions (MPE) are associated with poor prognosis, with a median survival of 6 months. However, there is a wide variation in survival. Predicting prognosis is important in determining treatment. In heart failure and idiopathic pulmonary disease, breathlessness is associated with poor prognosis. Objective: To determine whether breathlessness following pleural drainage is associated with survival in patients with MPE. Methods: A post-hoc analysis of patients in the TIME2 (chest drain and pleurodesis versus indwelling pleural catheter in patients with MPE, JAMA 2012; 307: 2383–9) and TIME3 (intrapleural fibrinolytics versus placebo in patients with non-draining MPE, AJRCCM 2018; 197: 502–508) randomised trials. In both studies, average breathlessness over the last 24 hours was measured using the validated 100 mm visual analogue scale (VASD). Minimal important difference is 19 mm. Subjects assessed their breathlessness at baseline and, following drainage, completed a daily diary for 42 (TIME2) or 28 (TIME3) days. Survival was measured in days from randomisation to death. Follow up was for 1 year. Cox regression was used to identify associations between breathlessness and survival. Responders were defined as patients with a reduction in mean post-drainage VASD of ³19 mm. Results: The study included 177 patients. Mean baseline VASD was 50 mm (SD 27). Median survival was 83 days (IQR 33–288). There was no significant association between baseline VASD and survival (p=0.563). The association between mean post-drainage VASD and survival was highly significant (hazard ratio per 1 mm increase in mean VASD 1.02, 95% CI 1.01 to 1.03; p<0.001). The difference in survival between responders and non-responders was highly significant (log rank test p<0.001). Conclusion: In these patients, there was a significant association between mean post-drainage VASD and survival. Patients who did not respond symptomatically to pleural fluid drainage had a worse survival than those who did. A limitation of this study is that it was a retrospective analysis of patients enrolled into two clinical trials, so results may not apply to all patients with MPE. Further research into the association between breathlessness and survival is needed.